2015
DOI: 10.1002/pc.23900
|View full text |Cite
|
Sign up to set email alerts
|

Damage characterization of three point bended honeycomb sandwich structures under different temperatures with cone beam computed tomography technique

Abstract: This study investigates the effect of different temperatures on the flexural properties of honeycomb sandwich structures which have a commercial code as Gillfloor 5424. Flexural properties of honeycomb sandwich structures were determined under three different temperatures (−20°C, 20°C, and 40°C). The results obtained from honeycomb sandwich structures were correlated with a function of core shear ultimate stress, facing stress, flexural stiffness and bending modulus of the sandwich panel. Moreover, cone beam c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Table 10 shows a comparison between the main properties of the proposed honeycomb panels and an all-aluminium based honeycomb designed for airplane structure (Gillfloor 5424), used the aisle and cargo floors of a Boeing 737-800 aircraft [46]. The proposed bottle caps core with aluminium skins and epoxy polymer exhibits 39% increased absolute flexural properties compared to the panel based on aluminium honeycomb.…”
Section: Comparative Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Table 10 shows a comparison between the main properties of the proposed honeycomb panels and an all-aluminium based honeycomb designed for airplane structure (Gillfloor 5424), used the aisle and cargo floors of a Boeing 737-800 aircraft [46]. The proposed bottle caps core with aluminium skins and epoxy polymer exhibits 39% increased absolute flexural properties compared to the panel based on aluminium honeycomb.…”
Section: Comparative Analysismentioning
confidence: 99%
“…The proposed bottle caps core with aluminium skins and epoxy polymer exhibits 39% increased absolute flexural properties compared to the panel based on aluminium honeycomb. Akatay et al [46] reported the absolute properties and the weight per unit area of the panel. Considering the thickness of the panel, an approximate equivalent density of the sandwich panel is determined, from which the specific flexural stiffness can be estimated.…”
Section: Comparative Analysismentioning
confidence: 99%
“…The skins are fabricated using unidirectional E‐glass fiber of 220 g/m 2 and reinforced with epoxy L/hardener EPH 161 (MGS Poxy‐systems) using hand layup, while the core is made of an aramid honeycomb (DuPont Nomex). The sandwich design is based on sandwich beam theory, combined with classical laminate theory and composite micromechanics models (see Appendix A1‐A3), which indicate that symmetric and balanced skins will limit the thermal and hygroscopic deformations due to temperature and humidity changes during processing and accelerated lifetime testing (ALT). Skins consisting of four unidirectional GFRP plies in a [0/90] s architecture (total thickness 0.8 mm) are thus combined with a 6 mm thick core to provide a sandwich with a theoretically computed stiffness of 14.96 N·m 2 .…”
Section: Methodsmentioning
confidence: 99%
“…In [6][7][8][9][10][11][12][13], the authors present further sandwich structures. The results of diagnostic methods suitable for sandwiches and their components are described in [14][15][16][17][18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%